Liberty, property and popular politics : England and Scotland, 1688-1815 : essays in honour of H.T. Dickinson - Pentland, Gordon; Davis, Michael T., 1969-; Dickinson, H. T. (Edinburgh University Press, 2016)
A broad, richly detailed examination of the cultural, political and social history of Britain's long eighteenth century. Few scholars can claim to have shaped the historical study of the long eighteenth century more profoundly than Professor H.T. Dickinson, who, until his retirement in 2006, held the Sir Richard Lodge Chair of British History at the University of Edinburgh. This volume, based on contributions from Professor Dickinson's students, friends and colleagues from around the world, offers a range of perspectives on eighteenth-century Britain and provides a tribute to a remarkable scholarly career. Professor Dickinson's work and career provides the ideal lens through which to take a detailed snapshot of current research in a number of areas. The volume includes contributions from scholars working in intellectual history, political and parliamentary history, ecclesiastical and naval history; discussions of major themes such as Jacobitism, the French Revolution, popular radicalism and conservatism; and essays on prominent individuals in English and Scottish history, including Edmund Burke, Thomas Muir, Thomas Paine and Thomas Spence. The result is a uniquely rich and detailed collection with an impressive breadth of coverage. Key features. Provides a snapshot of current research agendas in eighteenth-century history Features focused essays by an international team of contributors Includes fourteen chapters engaging with a range of historical sub-disciplines (including intellectual, parliamentary, political, ecclesiastical and naval history)